Modernization of ECR-source DECRIS-3 - Иванов , И.; Курахмедов , А.; Самбаев, Е.; Здоровец , М.; Логинов , В.; Богомолов , С.; Бондарченко , А.; Колобердин, М.; Сапар , А.; Унгарбаев, Е.; Темір , А.; Мустафин , Д.; et al. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The heavy ion accelerator DC-60 is equipped with an ECR source DECRIS-3. The source of multiply charged ions is designed to produce a beam of ions of various elements with a degree of ionization ≥ 1. The obtained beam of multiply charged ions, after selecting the required charge, can be injected into an accelerator to obtain a higher energy, or transported to a physical installation for experiments with a low energy beam. This article describes the main characteristics of the DECRIS-3 ECR source. In the course of operation at the DC-60 cyclotron, prerequisites appeared for improving the characteristics of the ECR source, and also during the operation, the characteristics of the magnetic field of the source worsened, all this led to the realization of the need to modernize the ECR source. Improving the characteristics of the ECR source makes it possible to increase the spectrum of capabilities of the cyclotron, which opens up new prospects for experimenters. A technical justification and terms of reference for the modernization of the ECR source were made jointly with Nuclear Reaction Laboratory staff of the Joint Institute for Nuclear Research and the authors of the research. Changes in the ECR source are shown schematically, and the magnetic field is calculated. Constructive changes in the source will make it possible to obtain more highly charged and high-intensity ion beams, which expands the capabilities of the DC-60 cyclotron